2013
DOI: 10.1210/en.2012-2145
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming: Impact of Prenatal Testosterone Excess on Insulin Sensitivity, Adiposity, and Free Fatty Acid Profile in Postpubertal Female Sheep

Abstract: Prenatal T excess causes reproductive and metabolic disruptions including insulin resistance, attributes of women with polycystic ovary syndrome. This study tested whether increases in visceral adiposity, adipocyte size, and total free fatty acids underlie the insulin resistance seen in prenatal T-treated female sheep. At approximately 16 months of age, insulin resistance and adipose tissue partitioning were determined via hyperinsulinemic euglycemic clamp and computed tomography, respectively, in control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 74 publications
(108 reference statements)
3
28
1
Order By: Relevance
“…Importantly, the window of susceptibility for developing insulin resistance was found to be confined to a shorter programming window, namely 60–90 days of gestation [41]. Interestingly, at postpubertal time points (~16 mo of age), insulin sensitivity is increased, visceral adiposity and adipocyte size are reduced, and circulating palmitic acid is increased in prenatal T females [112]. Relative to earlier observations of reduced insulin sensitivity during early life and adulthood, these findings of increased insulin sensitivity and reduced adiposity postpubertally are suggestive of a period of developmental adaptation.…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…Importantly, the window of susceptibility for developing insulin resistance was found to be confined to a shorter programming window, namely 60–90 days of gestation [41]. Interestingly, at postpubertal time points (~16 mo of age), insulin sensitivity is increased, visceral adiposity and adipocyte size are reduced, and circulating palmitic acid is increased in prenatal T females [112]. Relative to earlier observations of reduced insulin sensitivity during early life and adulthood, these findings of increased insulin sensitivity and reduced adiposity postpubertally are suggestive of a period of developmental adaptation.…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…Interestingly, the impact of postnatal T-treatment on fat deposition in rats appears to be a function of the strain used with some showing an effect and others not [68, 71]. Visceral adiposity does not appear to be a feature of prenatal T-treated sheep during their postpubertal life [72]; in contrast these females manifest reduced visceral adiposity similar to that of lean women with PCOS [73]. An imbalance in the plasma lipid profile is evident in prenatal and postnatal T-treated rat models reflected as an increase in triglycerides and cholesterol [68, 70].…”
Section: Adult Metabolic Phenotype Of Pcos Modelsmentioning
confidence: 99%
“…An imbalance in the plasma lipid profile is evident in prenatal and postnatal T-treated rat models reflected as an increase in triglycerides and cholesterol [68, 70]. An imbalance in free fatty acid is also found in monkeys [74] and sheep [72]. No metabolic disruptions have been reported in the letrozole-treated rat model [30].…”
Section: Adult Metabolic Phenotype Of Pcos Modelsmentioning
confidence: 99%
“…Increased maternal T produces at least two major potential effects: direct actions of T on the fetus and indirect actions on the maternal-fetal unit, which result in intrauterine growth retardation and chronic conditions in adult life, such as hypertension, dyslipidemia, and diabetes mellitus. 1-6 Numerous studies have demonstrated that T directly causes fetal damage. 7-11 On the other hand, the adverse effects of T on fetal growth could be from indirect action of T on the maternal-fetal unit and the uteroplacental circulation.…”
Section: Introductionmentioning
confidence: 99%